Development of a two-layer agentic architecture for automated generation and validation of wagon user interface schemas using multimodal large language models - Dobrovolskyi, Ivan (Eastern-European Journal of Enterprise Technologies, 2026)
The object of the study is automated generation and validation of wagon interface schemas in railway ticket booking systems. Manual updating of one configuration takes approximately 24 hours. It depends on software releases, requires engineer involvement, and increases the risk of production errors. A two-layer agentic architecture is proposed. It includes separation of reasoning and execution, multimodal conversion of schematics into structured configurations, and deterministic validation. The architecture was tested on the Ukrzaliznytsia platform. The platform supports more than 150 wagon configurations and serves over 20 million passengers per year. Twenty production schematics of different wagon classes were processed. One schematic required manual correction. The others were refined through one or two additional prompts. The time required to create a new wagon type decreased from approximately 24 hours to 15 minutes. This corresponds to an approximately 99% reduction. Monthly engineering involvement was largely replaced by a serverless workflow with infrastructure costs of less than 5 USD per month. No incidents caused by model hallucinations were recorded. The solution supports more than 150 configurations without loading all schemas into a single context. It enables non-technical administrators to update configurations outside release cycles and reduces dependence on engineering teams. The approach integrates mandatory pre-deployment validation into the configuration creation process. Structure, format, and correctness remain subject to formal control. This reduces manual engineering work without changes to the core application code. The approach is applicable to railway ticketing and related systems where physical objects are represented as digital interface schemas